Energy pricing policy: a few methodological comments for developing countries. (4th August 2014) - Percebois, Jacques
This paper analyses the theoretical aspects of energy pricing in developing countries. It shows that an energy pricing system is generally the result of historical events and seldom the consequence of a rational policy. It stresses how difficult it is to use energy prices to reach precise economic goals because of various constraints: users' reactions, external effects, equipment costs, etc. But, in spite of these difficulties, the price of energy remains a signal for users, even for the least rational ones.